(untitled) (Mustansiria Dental Journal, 2024)
Aim of the study: The present study aimed to evaluate the effect of surface treatments of zirconia (sandblast with 50µm Al2O3, 0.01M NaOH) on the shear bond strength between zirconia substructure and veneering porcelain. Materials and methods: Twenty-one (21) disk shape zirconia specimens were prepared with dimensions of (10mm) in diameter and (1mm) in height and sintered according to manufacturer instruction. Specimens were divided into three groups (n=7) according to surface treatment method; control group (C), sandblast with 50µm Al2O3 (SB), and sodium hydroxide (Na). Porcelain veneer (IPS-emax ceram, vita Germany) was applied on the zirconia specimens (5mm in diameter and 3mm in height) and fired according to manufacturer instruction. All specimens were then evaluated for shear - bond strength in a universal testing machine at 1mm/min cross head speed. The shear - bond strength value was then statistically analyzed with one-way ANOVA and LSD. Results: The result of the present study showed that 0.01M NaOH has significantly effect on the shear bond strength between zirconia and porcelain than sandblast with 50µm Al2O3. Conclusion: Sandblast with 50µm Al2O3 had no effect on the shear bond strength between zirconia substructure and veneering porcelain whereas 0.01M NaOH reduced the shear bond strength between them.